The Effect of Capital Expenditure on Local Revenue: Study In East Java Indonesia - Triyanto, Danang; Wahyudi, Setyo Tri; Ananda, Candra Fajri (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252)DO - 10.24843/JEKT.2017.v10.i02.p04, 2017)
In the decentralization era, local independence is the logic consequence of the implementation of fiscal decentralization. Further, fiscal decentralization has potentially to increase economic efficiency of the local government if compared with the central government. This research analyzed the effect of capital expenditure through Regional Gross Domestic Product (RGDP) on Local Revenue. The sample in this study was 38 districts/ cities in East Java province in Indonesia using path analysis. The results showed some findings, first, capital expenditures which divided into productive capital expenditures and less productive capital expenditures has affect on regional gross domestic product. Second, regional gross domestic product has affects on the forming components of local revenue. Furthermore, less productive capital expenditures and productive capital expenditures have indirect effect on local revenue through regional gross domestic product.
Keywords: fiscal decentralization, capital expenditure, regional gross domestic product, local revenue